Antioxidant and antimicrobial properties of dihydroquercetin esters (Brazilian Journal of Pharmaceutical Sciences, 2022)
Flavonoids display various beneficial biological properties, such as antioxidant activity and low cytotoxicity, which make them useful ingredients in foods, pharmaceuticals, and functional cosmetics. In particular, dihydroquercetin (DHQ) is found in various forms, and its derivatives exhibit interesting biological properties. Herein, we report the synthesis of acetylated and butyrylated dihydroquercetin derivatives and their antimicrobial and antioxidant properties. The DHQ derivatives were identified using 1H and 13C NMR spectroscopies and high-performance liquid chromatography combined with quadrupole time-of-flight mass spectrometry. The chemical stabilities of the acetylated dihydroquercetin derivatives were found to depend on the number of acetate groups, with 3,3',4',4,7-pentaacetyldihydroquercetin found to be the most stable acetylated dihydroquercetin. Furthermore, 7,3',4'-triacetyl- dihydroquercetin exhibited potent antioxidant activity, with an IC50 of 56.67 ± 4.79 μg/mL in the 1,1-diphenyl-2-picrylhydrazyl assay, with DHQ exhibiting a value of 32.41 ± 3.35 μg/mL. The reactive-oxygen-species-scavenging activity of 7,3',4'-triacetyldihydroquercetin was highest among the esters in the ferric reducing ability of plasma assay, but lower than that of DHQ. Overall, both DHQ and 7,3',4'-triacetyldihydroquercetin exhibited antimicrobial behavior against S. aureus and P. acnes using the paper disc assay. DHQ displayed a higher antimicrobial activity, with minimum inhibitory concentrations of 625 μg/mL (P. acnes), 2,500 μg/mL (S. aureus), and 5,000 μg/mL (E. coli). DHQ and acetylated dihydroquercetins are potentially useful as complex antioxidant and antimicrobial materials.